KEJAHATAN PORNOGRAFI TERHADAP ANAK DI DUNIA MAYA - Thresia Hilda Mathelda Yenkase Krey; Winna Amelia Alfrida Senandi (LPPM Uncen, 2023)
This science and technology implementation activity was carried out through counseling entitled